Technology Based Business Idea Blueprint (MUDA Enterprise) / Muhamad Danial Hairudin - Hairudin, Muhamad Danial (2020)
MUDA Enterprise have new product to introduce to the consumers which is the BRAVA. My company is targeting in supply for broom since it is people daily routine to clean their houses. BRAVA is a customer- friendly which is helps people saving time and energy to clean floor. Overall marketing strategy will be included specific marketing philosophy and strategy of the company, the value chain and the channel of distribution in the target market.My target customer is for households. The price is also reasonable. My company target for production in second year we will target to increase. The management team in our company consist of several sections and is conducted by experienced employee to make sure our company is run efficiently